2021
DOI: 10.1016/j.clnu.2020.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of sugars: A window to the regulation of glucose and lipid homeostasis by splanchnic organs

Abstract: Background &aims: Dietary sugars are absorbed in the hepatic portal circulation as glucose, fructose, or galactose. The gut and liver are required to process fructose and galactose into glucose, lactate, and fatty acids. A high sugar intake may favor the development of cardio-metabolic diseases by inducing Insulin resistance and increased concentrations of triglyceride-rich lipoproteins. Methods: A narrative review of the literature regarding the metabolic effects of fructose-containing sugars.Results: Sugars'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 71 publications
1
33
0
2
Order By: Relevance
“…Sucrose and high-fructose corn syrup are both composed of near-equal amounts of glucose and fructose. There is rising evidence that in these sweeteners, fructose and, in a lesser extent, glucose favor the development of metabolic diseases associated with sugar intake (7)(8)(9)(10). Obesity-associated chronic low-grade inflammation characterized by high levels of plasmatic inflammatory markers [C-reactive protein, interleukin 6 (IL6) or tumor necrosis factor a (TNFa)] largely contributes to the development of the obesityrelated chronic metabolic diseases (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Sucrose and high-fructose corn syrup are both composed of near-equal amounts of glucose and fructose. There is rising evidence that in these sweeteners, fructose and, in a lesser extent, glucose favor the development of metabolic diseases associated with sugar intake (7)(8)(9)(10). Obesity-associated chronic low-grade inflammation characterized by high levels of plasmatic inflammatory markers [C-reactive protein, interleukin 6 (IL6) or tumor necrosis factor a (TNFa)] largely contributes to the development of the obesityrelated chronic metabolic diseases (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Differential functional pathway analysis of the gut microbiota revealed that fructose and mannose metabolism was significantly enriched in mice fed high-AGE diets. Excess fructose can lead to insulin resistance and metabolic syndrome, 42 and Jaiswal et al 43 reported that fructose- This study has several limitations. First, we confirmed the association between gut bacteria (especially butyrateproducing bacteria) and insulin resistance, exclusively in mice fed high-AGE diets.…”
Section: Discussionmentioning
confidence: 87%
“…Differential functional pathway analysis of the gut microbiota revealed that fructose and mannose metabolism was significantly enriched in mice fed high-AGE diets. Excess fructose can lead to insulin resistance and metabolic syndrome, 42 and Jaiswal et al 43 reported that fructose-induced generation of reactive oxygen species impairs glucose utilization and insulin signaling in skeletal muscle cells. In the present study, fructose metabolism may have altered glucose homeostasis, resulting in insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The liver is a metabolic organ that is responsible for glucose and lipid homeostasis, drug metabolism, and bile synthesis ( Diehl-Jones and Askin, 2002 ; Almazroo et al, 2017 ; Tappy, 2021 ). Liver diseases contain non-alcoholic fatty liver disease (NAFLD) and its related diseases, drugs or infections induced liver injury, liver cancer, and among others.…”
Section: Introductionmentioning
confidence: 99%